Marteiliosis in molluscs - KARAGIANNIS (Δ. ΚΑΡΑΓΙΑΝΝΗΣ), D.; ANGELIDIS (Π. ΑΓΓΕΛΙΔΗΣ), P. (Journal of the Hellenic Veterinary Medical Society, 2017)
The protozoans, belonging to the phylum Paramyxea and particularly to the genera Marteilia, are the more important mollusc pathogens. The last thirty years marteiliosis has caused economic losses in mollusc aquaculture worldwide. According to the World Organisation for Animal Health (O.I.E.), it is not a zoonosis and it is classified in List II that includes mollusc diseases which are an obligatory statement in the European Union. The disease is characterized by progressive loss of body-weight of the infected shellfish and alteration of the colour of the digestive gland. Because of the absence of pathognomonic symptoms, histological and molecular techniques are required for the diagnosis of the disease. In Greece, marteiliosis constitutes a continuous threat for the mollusc aquaculture and demands surveillance and proper management. Genetic improvement of host species, in order to produce individuals resistant to the disease, as well as knowledge of the biology of Marteilia sp. constitute useful tools for the reduction of the impact of marteiliosis.